PH-Dependent Catalytic Behavior in Cathodic Application of Hydrogen Peroxide with Cobalt Oxide Modified Electrode and Its Application in Electrochemical Fenton Process in Alkaline Media. Issue 7 (1st January 2018) - Lin, Ya-Ting; Chen, Chi-Hao; Lin, Meng-Shan
Abstract : This work provides a novel scheme for performing an electrochmical Fenton-like (E-Fenton) process in alkaline media. In contrast to a typical Fenton process, we found that Cox Oy /H2 O2 possesses higher catalytic capability in an alkaline medium and that its related E-Fenton reaction can be carried out at −0.1 V (vs. Ag/AgCl). By investigating the electrochemical and the fluorescent behavior between cobalt oxide and hydrogen peroxide, the results show that maintaining the cobalt oxide in its low oxidation form, CoO (II), is the key step in decomposing hydrogen peroxide to form free radicals. Other oxidation states, such as Co3 O4 and CoOOH, do not possess sufficient catalytic capability to perform the Fenton reaction. Besides, we found the oxygen is one of the products in this system, but becomes an inhibitor to consume the active oxidation state, CoO (II). However, the influence of oxygen decreases with pH, and the efficiency of decomposing hydrogen peroxide can be performed significantly in alkaline solutions. Finally, this scheme was demonstrated by treating wastewater containing Reactive Blue 19 (RB19) at a concentration of 200 mg/L. After applying a potential of −0.1 V on a cobalt oxide modified electrode for 120 minutes, the color of RB19 can be completely removed.